Safety and efficacy of l‐cysteine hydrochloride monohydrate produced by fermentation using Escherichia coli KCCM 80180 and Escherichia coli KCCM 80181 as a flavouring additive for all animal species. (10th February 2020) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of l ‐cysteine monohydrochloride monohydrate produced by fermentation using two genetically modified strains of Escherichia coli K12 ( Escherichia coli KCCM 80180 and Escherichia coli KCCM 80181) as a flavouring additive for all animal species. No safety concerns are derived from the use of these strains as production strains of the additive. The FEEDAP Panel concludes that l ‐cysteine hydrochloride monohydrate, produced by E.coli KCCM 80180 and KCCM 80181 at concentrations up to 25 mg/kg complete feed, is safe for the target species, for the consumer and for the environment. The product is proposed to be classified as respiratory irritant; however, exposure by inhalation is unlikely. l ‐Cysteine hydrochloride monohydrate produced by E.coli KCCM 80180 and E.coli KCCM 80181 was shown to be a skin and eye irritant but not a skin sensitiser. Since l ‐cysteine hydrochloride monohydrate is used in food as flavouring, it is to be expected that it can provide a similar function in feed and no further demonstration of efficacy is necessary when used at concentrations up to 25 mg/kg complete feed and the corresponding concentration in water.